Nurse Telephone Counseling Services as a "Gatekeeper" in an Internet-Based Digital Doctor Reception: A Mixed Questionnaire Survey - Anders Johansson; Bodil Ivarsson (SAGE Publishing, 2019)
Objective: A large number of different types of digital innovations for health and medical care have been developed in Sweden under the concept of eHealth. Employees' interest is of great importance in determining the success of different new digital interventions and technologies. Purpose: In this study, we aimed to elucidate the nurses' experiences as a first "gatekeeper" in an Internet-based Digital Doctor Reception (DDR) concept. Methods: Our 16 informants were recruited among nurses who participated in a DDR pilot project that was completed in April 2019. A mixed questionnaire survey was used to elucidate the nurses' experiences of collaboration & challenges, technical functionality, and DDR as an activity. The results were descriptively summarized with index values (IVs, 0-1.0), supplemented with a 10-point Likert-type scale that estimated satisfaction and views regarding personal experiences. Results: Collaboration and challenges were experienced as fairly good (IV, 0.58), and technical functionality was experienced as good (IV, 0.80). The experience of DDR as an activity was described positively with an IV of 0.75. The overall experience of the concept (IV, 0.68), corresponds well to the median satisfaction value of 6.5 (interquartile range, 6-9). Content analysis identified 2 main categories: "Facilitators in using DDR experienced by nurses" and "Barriers in using DDR experienced by nurses." Nurses generally felt positive about participating in the development of an eHealth service. However, they suggested that DDR triaging should take place at the health care center level. The nurses also observed that certain patient groups were excluded from the DDR concept, and sometimes experienced this new way of triaging as less challenging. Conclusion: The informants in our study generally described satisfaction and an overall good experience with the DDR concept. However, some informants felt that the concept was sometimes more stressful and less challenging compared with normal working methods.